Chemical Properties of Biochar from Date Palm Seed (Phoenix dactylifera L.) under Low Temperature Pyrolysis as Soil Amendment Candidate (Applied Research in Science and Technology, 2021)
The waste of date palm seeds is abundant in Indonesia, however, the seeds are still regarded as trash from the manufacture of date palm-based products. Dates seed, when processed further, can be a useful resource, one of which is as a raw material in the production of Biochar. The utilization of date palm seeds into biochar is one strategy that can be applied. The purpose of this study was to determine the chemical properties of biochar derived from the seeds of palm date (Phoenix dactylifera L.). Making biochar is done by burning the seeds using a furnace with a temperature of 250°C and 350°C, then ground and sieved with a size of 350 micrometers carried out at the Research Center for Limnology and Water Resources. Chemical property analysis using X-Ray Fluorescence Spectrometer (XRF) at the Lampung Advanced Characterization Laboratory- BRIN. The results show there are four macronutrients found in date palm seed biochar namely P, K, Ca, and S. Most composition is Potassium (K). The potassium content of biochar burned at 250 °C is 66.24% while the biochar burned at 350 °C contains 67.189%. In addition, the phosphorus (P) content of biochar burned at a temperature of 250 °C is 6.574% while the biochar burned at a temperature of 350 °C contains 7.429%. Increasing the temperature increases the percentage of Potassium and Phosphorus, but the opposite results in Sulfur (S) and Calcium (Ca).